ANALISIS FUNDAMENTAL UNTUK MENILAI KEWAJARAN HARGA SAHAM PADA PERUSAHAAN SEKTOR ENERGI YANG TERDAFTAR DI BEI - Nathasya Indriwan (2022)
This research is a quantitative research that has the aim of knowing the fair value of a stock using fundamental analysis, which focuses on the Free Cash Flow to Equity (FCFE), Free Cash Flow to Firm (FCFF), Dividend Discount Model (DDM), and Price methods. Earning Ratio (PER). The research was conducted comparing market value with intrinsic value, resulting in undervalued, overvalued, or fair-valued shares. The sample in this study is the energy sector company listed on the IDX, where the company has published financial reports and has distributed dividends in the 2021 period. By using purposive sampling technique, 22 companies are produced that can be used as samples. This study uses the Root Mean Square Error (RMSE) test to find out which method is more accurate for valuing stocks. The RMSE test results show that the DDM method is a more accurate method than the FCFE, FCFF, and PER methods, because DDM has the smallest RMSE test value compared to the FCFE, FCFF, and PER methods.